2022
DOI: 10.1097/bpo.0000000000002267
|View full text |Cite
|
Sign up to set email alerts
|

Do’s and Don’ts in Primary Aneurysmal Bone Cysts of the Proximal Femur in Children and Adolescents: Retrospective Multicenter EPOS Study of 79 Patients

Abstract: Background: Aneurysmal bone cysts (ABC) are rare benign cystic bone tumors, generally diagnosed in children and adolescents. Proximal femoral ABCs may require specific treatment strategies because of an increased pathologic fracture risk. As few reports are published on ABCs, specifically for this localization, consensus regarding optimal treatment is lacking. We present a large retrospective study on the treatment of pediatric proximal femoral ABCs. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The authors identified “numerous forms of therapy” independent of localisation, including curettage and radiation but no stabilisation techniques. In the recently published retrospective multicentre EPOS study, in which 79 patients with ABC on the proximal femur were examined, no detailed information on the selection of the osteosynthesis technique, especially in the immediate vicinity of the growth plate, was provided [ 19 ]. The transphyseal screws we used were also not mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors identified “numerous forms of therapy” independent of localisation, including curettage and radiation but no stabilisation techniques. In the recently published retrospective multicentre EPOS study, in which 79 patients with ABC on the proximal femur were examined, no detailed information on the selection of the osteosynthesis technique, especially in the immediate vicinity of the growth plate, was provided [ 19 ]. The transphyseal screws we used were also not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…As an open procedure was chosen by 43% of our respondents and 44% of the participants of the EPOS multicentre study [ 19 ], in our opinion, there is nothing to be said against a plate osteosynthesis, which does not significantly exceed the extent of the intervention. From our point of view, immobilisation using an HSC offers, at best, an alternative if the procedure is not open.…”
Section: Discussionmentioning
confidence: 99%
“…Many sclerotherapies have been described with different sclerosants and application techniques. Some like sodium tetradecyl sulfate are injected with air to create a foam [ 25 ▪ ], while others like polidocanol are injected as liquids [ 5 ▪▪ ]. Sometimes combinations with embolizing substances are administered, aiming for increasing safety [ 26 ▪▪ ].…”
Section: Percutaneous Proceduresmentioning
confidence: 99%
“…Spinal lesions in general have received a substantial amount of interest recently, with multiple studies showing effectiveness of sclerotherapy in this vulnerable anatomical location [ 25 ▪ ]. In their cervical spine ABC series, Wong et al reported one treatment-related complication after doxycycline injection in a C2 ABC leading to sclerotherapy triggered spasm of the right posterior inferior cerebellar artery, resulting in distribution area infarction [ 31 ].…”
Section: Treating Aneurysmal Bone Cysts In Rare Locationsmentioning
confidence: 99%
“…The primary sites of manifestation are the proximal humerus and femur ( 1 ). Treatment objectives for these cysts include preventing pathologic fractures, promoting healing, and minimizing recurrence ( 2 ). Currently, strategies to promote cyst healing encompass a range of interventions, including steroid injections, curettage and grafting, internal fixation, or a combination thereof.…”
Section: Introductionmentioning
confidence: 99%